2022
DOI: 10.1186/s42077-022-00224-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided quadratus lumborum block versus transversus abdominis plane block in patients undergoing total abdominal hysterectomy

Abstract: Background Ultrasound (US)-guided quadratus lumborum block (QLB) and transversus abdominis plane block (TAP) are used as a part of multimodal analgesia for postoperative pain after abdominal procedures, as they improve postoperative pain. Results QLB group showed significantly better visual analog score (VAS) scores from 6 h till 24 h postoperative. Time for the first request for pethidine was significantly longer in the QLB group (398.3 ± 23.7 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Consistent with our findings, Jadon et al [19] concluded For women having a caesarean section, QLB extends the duration of pain relief and reduces the need for supplementary analgesics in comparison to the TAP block. Similar to our finding, Alansary et al [20] determined that QLB administered after total abdominal hysterectomy (TAH) was more efficacious in alleviating visceral and somatic pain compared to TAP block. Based on the findings reported by Oksüz et al [21] , it was determined that the QLB offered more prolonged and efficacious postoperative analgesia in paediatrics receiving orchiopexy or unilateral surgery of an inguinal hernia when compared to the TAP block.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, Jadon et al [19] concluded For women having a caesarean section, QLB extends the duration of pain relief and reduces the need for supplementary analgesics in comparison to the TAP block. Similar to our finding, Alansary et al [20] determined that QLB administered after total abdominal hysterectomy (TAH) was more efficacious in alleviating visceral and somatic pain compared to TAP block. Based on the findings reported by Oksüz et al [21] , it was determined that the QLB offered more prolonged and efficacious postoperative analgesia in paediatrics receiving orchiopexy or unilateral surgery of an inguinal hernia when compared to the TAP block.…”
Section: Discussionsupporting
confidence: 91%
“…This difference can be associated with a better spread of injection in SAM. [ 12 ] The results of our study are comparable to the study of El-Kabariety[ 13 ] which showed 100 mg tramadol used as an adjuvant with 20 ml of 0.5% levobupivacaine in transverse abdominis plane block had lesser morphine requirements in the first 48 h (18.1 ± 2.4 mg vs 26.1 ± 3.3 mg; P < 0.001) compared to levobupivacaine alone. However, the time to first morphine requirement was longer in our study group (6.11 ± 2.72 h vs 250.8 ± 23.3 min).…”
Section: Discussionsupporting
confidence: 85%
“…The previous studies have demonstrated the effectiveness of QLB in different types of abdominal operations, including cesarean section [25], [26], laparoscopic gynecological surgery [27], total abdominal hysterectomy [28], and other abdominal surgeries [29], [30]. A meta-analysis showed that QLB provides better pain management with less opioid consumption after abdominal surgery compared with TAP block [31].…”
Section: Resultsmentioning
confidence: 99%